CCAFS East Africa 2019–2021: Strategy for Supporting Agricultural Transformation, Food and Nutrition Security under Climate Change - Solomon, Dawit; Radeny, Maren A.O.; Mungai, Catherine; Recha, John W.M.; Schuetz, Tonya; Gadeberg, Marianne (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
East Africa has enormous potential, not only to feed itself and eliminate hunger, but also to be a major player in global food systems. This potential lies in its natural resources, its people and knowledge, and its huge markets. Agriculture represents a significant portion of this potential and constitutes a large part of East African economies. In Ethiopia, for example, agriculture contributed about 44% to the gross domestic product (GDP) over the past five years, while other East African countries generally attain about a third of their GDP from agriculture. The agriculture sector plays a key role for food and nutrition security, sustainable natural resources management and economic diversification. If leveraged, the sector could boost investment, increase intra-regional trade, provide employment opportunities, contribute to poverty eradication and foster human security, stability and prosperity.